2016
DOI: 10.5007/1518-2924.2016v21n47p16
|View full text |Cite
|
Sign up to set email alerts
|

Adoção da plataforma lattes como fonte de dados para caracterização de redes científicas

Abstract: ResumoOs estudos sobre dados de produções científicas têm recebido atenção de pesquisadores, de diversas áreas, que visam obter conhecimento sobre a evolução das pesquisas em geral. Tais estudos possibilitam a análise da produção científica para diversos propósitos e um dos desafios neste tipo de análise está na diversidade de repositórios contendo dados em formatos e estruturas distintas. Os currículos da Plataforma Lattes se caracterizam atualmente como importante ferramenta para que pesquisadores, acadêmico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…Such studies allow the analysis of scientific production for different purposes and one of the challenges in this type of analysis is the diversity of repositories containing data in different formats and structures. Lattes Platform curricula are currently characterized as an important tool for researchers, academics and students to record their data, being widely used, being characterized as one of the largest repositories of data on scientific, technical, artistic and professional production, containing millions of researchers registered (Dias, Moita & Dias, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies allow the analysis of scientific production for different purposes and one of the challenges in this type of analysis is the diversity of repositories containing data in different formats and structures. Lattes Platform curricula are currently characterized as an important tool for researchers, academics and students to record their data, being widely used, being characterized as one of the largest repositories of data on scientific, technical, artistic and professional production, containing millions of researchers registered (Dias, Moita & Dias, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…However, works found in the literature often focus on specific groups for analysis, especially when carrying out analyzes based on collaboration networks, since the frequently used techniques have a high computational cost (Dias, Moita & Dias, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…'Partially' because there is a reasonable number of full-time professors who have a stable career and do not show any interest in updating their profile. Dias et al [13] published a histogram of the number of Lattes CVs, among 4,156,635 (one per person) published by 5 April 2015, last updated on each date in 1997-2015. Roughly 60% and 40% of the curricula were not updated during the last 1.25 and 2.25 years, respectively, which reveals that either the scientific productivity of those professionals is low, and/or Lattes CV is not effective enough to be the first choice for those users.…”
Section: Use Of the Lattes CV Platformmentioning
confidence: 99%
“…'Partially' because there is a reasonable number of full-time professors that have a stable career and do not show any interest in upgrading it. Dias et al [11] published a histogram of the number of Lattes CVs, among 4.156.635 (one per person) published by April 5 th 2015, last updated on each date in 1997-2015, as shown in Figure 1. It is shown that roughly 60% and 40% of the curricula were not updated during the last 1.25 and 2.25 years, respectively, which reveals that either (i) the scientific productivity of those professionals is low, and/or (ii) Lattes CV is not effective enough to be the first choice for the vast majority of those users.…”
Section: Use Of the Lattes CV Platformmentioning
confidence: 99%